Predicting the Performance Anxiety of Musicians Based on Coping Strategies and Emotional Self-Regulation with the Mediation of the Conscious Mind - khodadadeh, Rahin; Momeni, Khoda Morad; jadidi, Hooshang; Akbari , Maryam (Journal of Clinical Physiotherapy Research, 2022)
Introduction: Music performance anxiety has been the focus of psychological research in recent years. The anxiety of music performance is a big problem which musicians, students of the music field are involved with, and at high levels this anxiety prevents the performance or even leads to an impact on the performance or even leaving the stage The aim of this study was to develop a causal model for predicting music performance anxiety based on coping strategies and emotional self-regulation mediated by mindfulness. Materials and Methods: This research was descriptive-correlation type. The statistical population of this study included all musicians, music teachers, and music students in Kermanshah (1,200 persons). A sample of 300 music students and musicians (according to Morgan's table) were selected as available sampling. In this study, information collection tools included 4 standard questionnaires of music performance anxiety of Kenny, Andler and Parker Coping Styles, emotional self-regulation of Garnfsky & Kreich, and the pentagonal mindset of Bayer et al. For inferential analysis of the data, the effects have been investigated using structural equation modeling and Smart PLS software. Results: The results showed that emotion-oriented coping style (β=0.04, T=6.50) and avoidance coping style (β=0.03, T=7.12) had a positive and significant effect on music performance anxiety, but problem-oriented coping style has a negative and significant effect (β=-0.05, T=-7.04). Also, positive cognitive-emotional self-regulation had a negative and significant effect (β=-0.08, T=7.73), and negative cognitive-emotional self-regulation had a positive and significant effect (β=0.04, T=7.10). There was a negative and significant effect between mindfulness and music performance anxiety (β=-0.26, T=5.74). Conclusion: Music performance anxiety is predictable and appropriate strategies can be used to control and reduce it. In this regard, it is important to educate and inform musicians about coping strategies, emotional self-regulation, and mindfulness.